Triflumezopyrim: a new mesoionic insecticide for the management of planthoppers in Paddy - Sarao, P S; Lakshmi, V Jhansi (Indian Journal of Plant Protection, 2020)
Triflumezopyrim 10.6% SC is a novel insecticide from a new mesoionic insecticide chemical group. Its bioefficacy was assessed against whitebacked planthopper (WBPH) and brown planthopper (BPH) for two crop seasons at 15, 25 and 35 g a.i. ha-1 along with imidacloprid 17.8 SL and quinalphos 25 EC at 20 and 500 g a.i. ha-1, respectively. Triflumezopyrim at 25 and 35 g a.i. ha-1 wasproved significantly effective in reducingWBPH (1.77-2.43 WBPH/hill) and BPH (2.00-3.97 BPH/hill) populations 3, 5, 10 and 15 days after spraying in rice fieldas compared to imidacloprid (2.40-7.27 hoppers/hill) and quinalphos (2.10-6.37 hoppers/hill). The riceyield in two doses (25 and 35 g a.i. ha-1) of triflumezopyrimwas statistically at par with each other (74.73-75.67q ha-1) but significantly better than check insecticides (72.60-73.33 q ha-1) and untreated control (69.47q ha-1). There was no significant difference in spider numbers among the various treatments at 10 and 15 days after sprayingduring both the years; indicating the safety of triflumezopyrim to spiders.